Cybersecurity value conflicts in coping at home health technology: Design science research towards ethical decision-making - Rajamäki, Jyri (Finnish Journal of eHealth and eWelfare, 2022)
The transition of health care and health services to information networks raises ethical challenges. Especially when designing digital solutions for older citizens, their rights and opportunities to live a good life at home or in a homelike environment must be taken into account. In this case, ethics and ethical expertise play a key role, from design to implementation and evaluation. Ethics need to be looked at from a variety of perspectives, but at the same time, unfortunately, there are often value conflicts between different ethical values and norms. This design science research examines ethical issues related to the cybersecurity of digital health services through four different reference frameworks: biomedical ethics, care ethics, the core functions of health information technology, and cybersecurity core value clusters. The research focuses on value conflicts between different perspectives and presents a conceptual model for the simultaneous consideration of these different frameworks to aid ethical decision-making. In addition, the article discusses ethical decision-making through fuzzy multi-criteria decision-making and considers the use of the digital twin produced through machine learning and homomorphic encryption in this context.